Research of nickel nanoparticles toxicity with use of Aquatic Organisms. Issue 1 (October 2015) - Morgaleva, T; Morgalev, Yu; Gosteva, I; Morgalev, S
Abstract: The effect of nanoparticles with the particle size Δ50 =5 nm on the test function of aquatic organisms was analyzed by means of biotesting methods with the use of a complex of test-organisms representing general trophic levels. The dependence of an infusoria Paramecium caudatum chemoattractant-elicited response, unicellular algae Chlorella vulgaris Beijer growth rate, Daphnia magna Straus mortality and trophic activity and Danio rerio fish kill due to nNi disperse system concentration, is estimated. It is determined that the release of chlorella into cultivated environment including nNi as a feed for daphnias raises the death rate of entomostracans. The minimal concentration, whereby an organism response to the effect of nNi is registered, depends on the type of test organism and the analysed test function. L(E)C20 is determined for all the organisms used in bioassays. L(E)C50 is estimated for Paramecium caudatum (L(E)C50 = 0.0049 mg/l), for Chlorella vulgaris Beijer (L(E)C50 = 0.529 mg/l), for Daphnia m. S (L(E)C50 > 100 mg/l) and for fish Danio rerio (L(E)C50 > 100 mg/l). According to the Globally Harmonized System hazard substance evaluation criteria and Commission Directive 93/67/EEC, nNi belongs to the "acute toxicity 1" category of toxic substances.